Interacting with Shakespeare's figurative language: a project in materials development for the L2 classroom - Lenahan, Patrick (Rhodes University, Faculty of Education, Department of Education, 1995)
This project arises from recent initiatives aimed at transforming Shakespeare studies in South African high schools, so as to make those studies more learner-centred and interactive, as well as a more useful communicative language-learning experience for second-language (L2) students. It is this interactive methodology that the present project seeks to extend to the relatively neglected area of Shakespeare's figurative language. Drawing on schema theory and response-based approaches to literature teaching, the project shows that figurative language is especially conducive to interactive treatment, whereby students might be encouraged to make sense of metaphors and similes out of their "background knowledge". Guidelines are indicated for putting this into practice in the L2 classroom; and on the basis of these guidelines, materials are developed for an interactive approach to Shakespeare's figurative language. The central phase in this development process involves trying out the materials in five African high schools and then analysing the data collected from them. The classroom try-outs were profitable in so far as they raised issues that had been overlooked in the earlier, theoretical, stage of the development process. A good overall response to the materials' learner-centred approach was indicated, although students experienced difficulties with certain essential tasks. Most seriously, while the materials were successful in accessing students' background knowledge in the form of associations, they were less successful in getting students to use this knowiedge in interpreting metaphors for themselves. Reasons for this feature, and others, are considered and solutions posited. Recommendations for implementing the materials in a larger teaching programme are made.
Keywords: Shakespeare, William, 1564-1616 -- Language; Shakespeare, William, 1564-1616 -- Study and teaching; English literature -- Study and teaching -- South Africa -- Foreign speakers; English language -- Study and teaching -- South Africa -- Foreign speakers